Impact of Corporate Governance on Financial performance: A Study on DSE listed Insurance Companies in Bangladesh (Global Journal of Management and Business Research, 2018)
Corporate governance involves promoting the compliance of law in letter
Keywords: corporate governance; listed insurance companies; board size; board audit committee; board composition; and return on equity